2014
DOI: 10.1371/journal.pone.0098610
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholders' Perceptions of Integrated Community Case Management by Community Health Workers: A Post-Intervention Qualitative Study

Abstract: BackgroundIntegrated community case management (iCCM) involves delivery of simple medicines to children with pneumonia, diarrhea and/or malaria by community health workers (CHWs). Between 2010 and 2012, an iCCM intervention trial was implemented by Healthy Child Uganda. This study used qualitative tools to assess whether project stakeholders perceived that iCCM improved access to care for children under five years of age.MethodsThe intervention involved training and equipping 196 CHWs in 98 study villages in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 15 publications
2
20
0
Order By: Relevance
“…This is in line with many other studies that have shown the acceptability of community case management of disease starting with diarrhea and malaria [51][52][53] and more recent research on iCCM including pneumonia care. 19,20 This is likely because the CHWs in this program have been providing services which are considered valuable to the community. 21 Previous work has demonstrated the availability of drugs as an exceedingly important component of iCCM interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with many other studies that have shown the acceptability of community case management of disease starting with diarrhea and malaria [51][52][53] and more recent research on iCCM including pneumonia care. 19,20 This is likely because the CHWs in this program have been providing services which are considered valuable to the community. 21 Previous work has demonstrated the availability of drugs as an exceedingly important component of iCCM interventions.…”
Section: Discussionmentioning
confidence: 99%
“…17 A recent meta-analysis showed that one of the most important aspects of scalable interventions with CHWs is community acceptance. 18 Although some studies have demonstrated that iCCM interventions are acceptable to the community, 19,20 others have shown that programs are resisted if CHWs do not provide services of value. 21 This is important because iCCM programs, which have low utilization and likely low acceptance of services are the least costeffective, do not lead to decreases in mortality, and may decrease demand for biomedical health care, leading the most marginalized to seek care from ineffective providers.…”
Section: Introductionmentioning
confidence: 99%
“…(ii) Household surveys As described by Buchner and colleagues 37 a household survey of mothers of young children was conducted in November 2012 in 15 randomly selected households per village. The tool was translated into the local language, back-translated, and field-tested prior to data collection.…”
mentioning
confidence: 99%
“…The tool was translated into the local language, back-translated, and field-tested prior to data collection. 37 Trained research assistants not involved in the study intervention administered surveys verbally. Treatment was determined 'appropriate' if the mother reported that the child received, in age-appropriate dosage, artemether-lumefantrine (Coartem ) for fever, an antibiotic for cough and rapid breathing, and ORS and zinc for diarrhoea.…”
mentioning
confidence: 99%
See 1 more Smart Citation